Compartilhando fotografias de natureza nas redes sociais: uma experiência midiática de ensino-aprendizagem das interações ecológicas - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
This paper proposed the investigation of the use of photographs of nature and scientific texts as part of a methodological construction for the teaching of ecological interactions, and the inclusion of a virtual learning object constituting itself as an instrument of computing resources that allows the interaction of the student. The methodology consisted in the development of teaching materials using digital photographs and scientific texts about ecological interactions, which were used in discussions mediated by the teacher through a social network: Facebook. The study involved students of the 3rd year of high school in a public state school in the city of Goiânia-GO. We opted for a quantitative and qualitative research, collecting qualitative data through questionnaires and conducting the content analysis of their ecological perceptions at the time of interaction in the social network. The results show that the inclusion of these technologies in education Ecology presented encouraging results providing the development of scientific literacy in students and that Facebook has proved a powerful and promising platform to be used in the teaching-learning process, the mold of other platforms used in distance learning still need further study on the behavior of young people in this social network to take advantage of this dynamic teaching.
Keywords: Ensino de Ecologia; Facebook; Imagens de natureza; Divulgação científica; Tecnologias da informação e comunicação (TIC); Ecology; Facebook education.; Nature images; Popular Science; Information and communication technologies (ICT); ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO; CIENCIAS BIOLOGICAS::ECOLOGIA